Research Trends and Development Patterns in Language Testing Over the Past Three Decades: A Bibliometric Study - Dong, Manxia; Gan, Cenyu; Zheng, Yaqiu; Yang, Runsheng (Frontiers in Psychology, 2022)
This study used bibliometric data from the prestigious international peer-reviewed journal in the language testing field, Language Testing, to investigate research trends and development patterns in language testing. The bibliometric information involved the number of publications, the most frequently researched test types and topics, the most cited publications and authors (as measured by references), the most prolific countries/regions and institutions and the most frequently collaborating countries/regions. The results showed that interest in language testing has been increased over time, regional tests and international tests have been major concerns, while classroom tests/assessments have received less attention. Research topics were wide-ranging and addressed almost all language testing related issues, among which validity/validation received the highest interest across periods. Moreover, the publications were produced by a wide range of countries/regions and institutions and included collaborative research spanning various institutions and regions, although collaborative publications across countries were relatively scarce. Based on the findings of this study, implications and suggestions have been highlighted for future research, academic agencies and this journal.